Developmental plasticity in amphibian larvae across the world: Investigating the roles of temperature and latitude - Sinai, Noa; Glos, Julian; Mohan, Ashwini V.; Lyra, Mariana L. [UNESP]; Riepe, Maya; Thöle, Elena; Zummach, Cecile; Ruthsatz, Katharina (Elsevier, 2022)
Temperature-induced developmental plasticity could allow amphibian larvae to complete metamorphosis successfully despite new thermal challenges and increased desiccation risk due to climate change. Here we investigated how the capacity for temperature-induced developmental plasticity varies with latitude and whether population-specific biogeographic background accounts for the different degree of plastic responses to temperature. We carried out a combined analysis based on the data from 150 studies (93 articles) performed on 64 amphibian species. We collected empirical data for age and size at metamorphosis in amphibian larvae acclimated to different temperatures during development and found that all larvae from all populations in these studies revealed a change in metamorphic traits with a given change in temperature and thus, were able to exhibit temperature-induced developmental plasticity. Age at metamorphosis was more affected by temperature than size at metamorphosis. Age and size at the onset of metamorphosis were generally lowest at warmest temperatures during development. Furthermore, populations from tropical latitudes were less sensitive to a change in developmental temperature compared to populations from higher latitudes. Accordingly, we suggest tropical populations to be the most vulnerable to increasing temperatures during metamorphosis. Our analyses reveal biases with respect to taxonomy, biogeographic distribution of species, and study design. Data from tropical populations are underrepresented and thus, the capacity for developmental plasticity of the most threatened species probably remains poorly understood. Future studies should focus on under-represented regions, most threatened species, and include a broader range of temperatures during development in order to make robust projections on future sensitivity of populations to climate change.
Keywords: Climate change; Conservation physiology; Metamorphosis; Phenotypic plasticity; Taxonomic bias; Temperature-size-rule